2016
DOI: 10.1088/1742-5468/2016/8/084007
|View full text |Cite
|
Sign up to set email alerts
|

Polydisperse hard spheres: crystallization kinetics in small systems and role of local structure

Abstract: We study numerically the crystallization of a hard-sphere mixture with 8% polydispersity. Although often used as a model glass former, for small system sizes we observe crystallization in molecular dynamics simulations. This opens the possibility to study the competition between crystallization and structural relaxation of the melt, which typically is out of reach due to the disparate timescales. We quantify the dependence of relaxation and crystallization times on density and system size. For one density and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Additionally, for the study of structural relaxation in supercooled liquids and glasses a size dispersity must be introduced to prevent crystallization even at very small packing fractions [6,12,13]. Despite their popularity as model glass formers, recent observations in bulk have revealed that Gaussiandistributed hard spheres [37][38][39][40] as well as the often used Kob-Anderson model [41,42] form crystals already in the supercooled regime. This crystallization is induced by a process called fractionation which describes the separation of a homogeneous fluid into different liquid or crystalline fractions with very different particle-size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for the study of structural relaxation in supercooled liquids and glasses a size dispersity must be introduced to prevent crystallization even at very small packing fractions [6,12,13]. Despite their popularity as model glass formers, recent observations in bulk have revealed that Gaussiandistributed hard spheres [37][38][39][40] as well as the often used Kob-Anderson model [41,42] form crystals already in the supercooled regime. This crystallization is induced by a process called fractionation which describes the separation of a homogeneous fluid into different liquid or crystalline fractions with very different particle-size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the binodal we use a polydisperse system to prevent crystallization. In our five-component system, small systems (N 500) can exhibit fluctuations to crystalline states [63], but for the system sizes we consider here we have never observed crystallization when the polydispersity δ ≥ 0.08 [23].…”
Section: Estimating the Liquid-vapour Binodalmentioning
confidence: 80%
“…Even for simple systems, it is challenging to uncover reaction coordinates for such highly cooperative transitions as occurring in nucleation and self-assembly. While optimal linear combinations of a set of candidate order parameters have been determined through maximum-likelihood methods, autoencoder architectures have the potential to uncover strongly nonlinear optimal mappings to reaction coordinates. Our results constitute a step toward a comprehensive computational understanding for multistep and hierarchical self-assembly through a combination of unsupervised dimensionality reduction of a set of structural descriptors with Markov state modeling.…”
Section: Discussionmentioning
confidence: 99%